Design and Manufacturing of Plastic Waste Recycling Equipment in Tumpuk Tangah Village - Panuh, Dedikarni; Astuti, Puji; Prayitno, Budi; Siwanto, Apri; Retno, Deddy Purnomo; Harmiyati, Harmiyati; Suhada, Egi; Che Isa, Nik Norziehana (Universitas Pahlawan Tuanku Tambusai, 2025)
Plastic waste is everywhere in almost all sectors, threatening the environment. Recycling is considered the best and most feasible option to overcome this danger. Tumpuk Tangah Sawah Lunto Village is a dense urban area with the potential to be a model for recycling waste. The waste recycling method designed for this service is melting plastic waste first. The waste-melting tool is used so that all plastic waste can be recycled. This research aims to provide education and create tools for recycling plastic waste. The machine developed is used to recycle plastic waste using a melter. In general, other features of this machine include a melting chamber, a burning chamber, and a vertical-type mixer. The tools designed are planned and comply with safety specifications. They are easy to operate, efficient, and low-cost. The people of Tumpuk Tangah Village can use this melting tool as an assisted village to recycle plastic waste.